Pengujian Keadaan Polisentrisitas: Gambaran Kasus Kota Bandung dan Sekitarnya - Kombaitan, B. (Journal of Regional and City Planning, 2001)
This paper aims to examine the pattern of urban spatial structure development, using Bandung as a case of Indonesian metropolitan cities during the period of 1980-1993. Monocentric, polycentric, and omnicentric density function models are explored respectively as a basis to be tested in metropolitan Bandung. It argues that the polycentric density functions statistically predict the better distribution of worker residences than monocentric ones. This finding suggests that polycentricism of spatial structure exists in metropolitan Bandung although it further shows that the dependence of worker residences to their job locations in central-city area is still existed.